1972
DOI: 10.2466/pms.1972.35.2.671
|View full text |Cite
|
Sign up to set email alerts
|

Normative Study of Oral Vibrotactile Sensitivity

Abstract: Ascending vibrotactile lingual thresholds were obtained for 110 Ss at 200 and 400 Hz. Mean thresholds and standard deviations were reported i n microns. Although frequency differences were observed, comparatively small standard deviations reflected little inter-subject variability. Possible clinical applications were discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
1

Year Published

1974
1974
1987
1987

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 16 publications
1
8
1
Order By: Relevance
“…This finding appears to conflict with the data of Verrillo (1966Verrillo ( , 1968 but is consistent with some of the data of Fucci and his colleagues (e.g., Fucci & Petrosino, 1982;Hall, Fucci, & Arnst, 1972;Telage et al, 1972). One interesting feature of Verrillo's (1968) lingual data, however, is that the presence of a surround did not significantly decrease the sensitivity to high-frequency vibration.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…This finding appears to conflict with the data of Verrillo (1966Verrillo ( , 1968 but is consistent with some of the data of Fucci and his colleagues (e.g., Fucci & Petrosino, 1982;Hall, Fucci, & Arnst, 1972;Telage et al, 1972). One interesting feature of Verrillo's (1968) lingual data, however, is that the presence of a surround did not significantly decrease the sensitivity to high-frequency vibration.…”
Section: Discussioncontrasting
confidence: 57%
“…The sensitivity of both oral structures remained constant between 60 and 900 Hz. However, a number of studies seem to contradict Fucci's data, indicating instead that frequency was a factor even when a surround was used (e.g., Fucci, Blackmon, Lindsey, & McCaffrey, 1974;Fucci, Crary, & Telage, 1977;Fucci, Curtis, & Harnack, 1974;Fucci, Hall, & Weiner, 1971;Telage, Fucci, & Arnst, 1972;Telage, Fucci, & Blackmon, 1976). Subsequent to those studies, Telage and Petrosino (1978) again obtained a relatively…”
Section: Barry G Green Monell Chemical Senses Center Philadelphia mentioning
confidence: 89%
“…More recent investigations have produced results in agreement with Sherrick's (I953) observation of a frequency-selective response on the dorsal lingual surface (Telage & Fucci, 1973, 1974Telage, Fucci, & Arnst, 1972). All of these recent investigations utilized a free surround disk in obtaining lingual vibrotactile thresholds.…”
supporting
confidence: 74%
“…The basic issue with respect to the methodology employed in this investigation and the methodology used by Verrillo ( 1963Verrillo ( , 1966 concerns the response characteristics of neural receptors found in the anterior dorsal surface of the tongue. In obtaining lingual vibrotactile thresholds as a function of frequency (Telage, Fucci, & Arnst, 1972), temporal summation (Telage, Fucci, & Blackmon, 1976), and spatial summation (present study), findings have consistently suggested the stimulation of a receptor population which responds selectively and specifically to vibration. These findings were obtained using three different vibrotactile stimulators of similar design.…”
Section: Fig 3 Graphic Representation Of Lingual Vibrotanile Threshmentioning
confidence: 75%
“…The application of cybernetic models for explaining the speech-production process suggested that haptic sensory feedback may provide neurological control for coarticulatory events (Fairbanks, 1954;Mysak, 1966). These models further implied that the development and coordinated use of motor speech patterns may to some degree be contingent upon the manner by which oral mechanoreceptors transduce sensory information, Early research in this area attempted to measure lingual vibrotactile sensitivity as a function of frequency (Fucci, 1972). Consistent findings demonstrated a differential response to frequency with maximum sensitivity occurring within a range between 250 and 400 Hz (Telage, Fucci, & Amst, 1972; Telage & Fucci, 1974% 1974b, 1975.…”
mentioning
confidence: 95%